Methods to promote Borreria latifolia seed germination (Revista Ciência Agronômica, 2018)
Specific knowledge on dormancy and germination patterns of weed species aids the development ofintegrated management strategies. This study aimed to evaluate and select effective methods for overcoming dormancy inB. latifolia seeds, as well as determining their influence on the germination process. A completely randomized experimentaldesign was used, with four replications and 20 seeds per repetition. Seven tests were conducted, with the corresponding B.latifolia seed treatments: Test 1 - mechanical scarification, sulfuric acid, hot water and running water; Test 2 - pre-coolingat 4 °C and dry heat at 60 °C. Test 3 - gibberellic acid at concentrations of 0, 50, 100, 200 and 400 ppm; Test 4 - aceticacid and potassium nitrate 2%; Test 5 - dual combinations of the three best treatments observed in the first four tests. Test6 - pre-soaking in a sandbox and in germination paper and; Test 7 - imbibition curve. The seeds were submitted to thegermination test in BOD at 25 °C with a photoperiod of 12h, in transparent polypropylene boxes. Germination percentage(GP), mean germination time and relative frequency of germination were determined and the weight of the seeds aftersoaking in Test 7 was measured. The best treatments for overcoming seed dormancy were dry heat, gibberellic acid 283ppm and KNO33h. The association of dry heat + potassium nitrate 3 h and potassium nitrate 3 h +gibberellic acid increasedgermination percentage by 25% compared to isolated treatments.